2021
DOI: 10.1002/rcr2.796
|View full text |Cite
|
Sign up to set email alerts
|

Enteral lorlatinib after alectinib as a treatment option in anaplastic lymphoma kinase‐positive non‐small cell lung cancer with triple problems: carcinomatous meningitis, poor performance status, and dysphagia—a case report

Abstract: Alectinib treatment is effective in patients with anaplastic lymphoma kinase (ALK) gene rearrangement‐positive non‐small cell lung cancer (NSCLC; hereafter ALK‐positive NSCLC) who exhibit central nervous system (CNS) relapse and poor performance status (PS). Lorlatinib treatment is effective upon failure of other ALK inhibitor‐based treatments. However, much remains unknown about the efficacy of lorlatinib in patients with ALK‐positive NSCLC, who have triple problems, carcinomatous meningitis, poor PS, and dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In this previous study, the patient with ALK + NSCLC with esophageal metastasis showed rapid improvement of dysphagia symptoms after 5 days of treatment with lorlatinib without local therapy. In another study similar to the present study, within three days, the patient's consciousness improved (26). In the present case, dysphagia and dyspnea improved after 6 days of treatment.…”
Section: Discussionsupporting
confidence: 87%
“…In this previous study, the patient with ALK + NSCLC with esophageal metastasis showed rapid improvement of dysphagia symptoms after 5 days of treatment with lorlatinib without local therapy. In another study similar to the present study, within three days, the patient's consciousness improved (26). In the present case, dysphagia and dyspnea improved after 6 days of treatment.…”
Section: Discussionsupporting
confidence: 87%
“…To prioritize the best candidates for DR-TLE, we thoroughly explored their safety profile and the information derived from the previous use of these drugs in epilepsy. For instance, there are clinical case reports and studies showing patients who developed seizures after being treated with melphalan for myeloma 73 , alectinib for lung tumors 74 , or vandetinib or gefitinib for glioma 75,76 . Moreover, gefitinib showed brain toxicity in a chronic epilepsy drug screening 77 .…”
Section: Discussionmentioning
confidence: 99%